The Advantages of Decentralized Government from the Viewpoint of Public Service Innovation - Fayth Elliott (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
With a decentralized government, power is not concentrated in one location but rather shared across several tiers of government. There are a number of benefits to using this method to innovate public services. For starters, it promotes decentralization, which in turn improves public services by being more responsive to local demands. Second, it makes government more accessible, thus increasing accountability, by making it more open and responsive to the needs of the people. Further benefits include increased citizen involvement and a lower overall cost to operate the government. Lastly, decentralization promotes innovation and new approaches to providing public services by allowing for trial and error. In general, decentralization of power can lead to better public service delivery and longer-term stability for local communities.